(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The present didactic paper describes the path of the stimulus control area until the proposition of the equivalence paradigm, defining and linking together the main concepts involved an its implications to the growing comprehension of complex behavioral processes such as verbal behavior learning , the notion of meaning and symbolic behavior in general. It presents the logic of Sidman´s first experiments, showing the inductive and careful way of the author until the point of presenting the equivalence paradigm and points the educational implications of the model (teaching economy, teaching procedures to reading, writing and mathematics behavior), as well asnewstudies of the area that promises implications to the clinic context.